(untitled) (Research, Society and Development, 2021)
The general objective of the research is to investigate the cultural identity of the Kaingang indigenous community residing in the city of Santa Maria-RS, Brazil. As for the specific objectives, we seek to carry out a historical rescue of the areas of the Brazilian territory inhabited by indigenous peoples, search websites and legal documents for information about these communities and describe the cultural identity of the Kaingang community residing in the city of Santa Maria-RS. For the accomplishment of the study, the instrument used was a documentary and bibliographic research, an interview and a questionnaire applied with the chief of the tribe. It was concluded that the Kaingang tribe seeks to preserve their cultural expressions and also tries to dialogue with public authorities for the resolution of conflicts. This tribe wishes to follow its history, its culture and also its insertion in the contemporary world reflexively in the face of the challenges imposed by the globalized society.